Desalination : discharging brine into coastal waters - Cher, Leo Wei Kwang. (2009)
The increase demand of fresh water due to the shortage of water has amplified the development of desalination technologies. This also brings problems such as discharging of concentrated brine into coastal waters that may give rise to potential and permanent damage to the marine ecosystem. Concentrated brine is a solution that has a higher density than seawater, thus causing them to be negatively buoyant. The brine tends to sink and spread along the seabed. Therefore, it is vital to find the techniques to enhance mixing of brine in the “allocated impact zone” thus preventing the spread of high salinity out of this region.